FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESEJAHTERAAN PSIKOLOGIS PADA PEKERJA PEREMPUAN BAGIAN PRODUKSI DI PT A INDONESIA TAHUN 2023 - Hernisa Shofwatulqolbi Ramadhani (2024)
Psychological well-being is a form of welfare that if not fulfilled, it will reduce the health, performance of workers, and detriment of the company's financial. In female production workers of PT A Indonesia, it was found that the level of psychological well-being was not optimal. This study aimed to determine the factors associated with psychological well-being in female production workers at PT A Indonesia. The research used quantitative methods with a cross-sectional study design and was conducted from October-December 2023. The sampling technique used simple random sampling with a sample size of 201 workers. Primary data were collected using questionnaires, namely Ryff's psychological well-being questionnaire, RSME questionnaire, WFCS questionnaire, and MSPSS questionnaire. Bivariate data analysis using chi-square test. The results found 52.2% of female workers experienced moderate psychological well-being. There is a relationship between high work family conflict (p-value = 0.002) and social support (p-value = 0.000) with psychological well-being. Workers are expected to make time for themselves, discuss the division of family duties with family members, and establish good relationships with other people. The company is advised to provide education to improve time management, increase the number of workers, and hold activities to foster a kinship, motivation, and welfare.